Government Efforts to Increase Community Empowerment Through Small and Medium Enterprises Entrepreneurship - Nur, Andi Cudai (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
SME development can be done through various government programs and activities, by involving various important elements of entrepreneurship, especially in empowering the community to be actively involved in SME activities. Sustainable expansion and diversification are very important for SME development, as well as making it the prima donna of the economic sector. This study aims to determine the government's breakthroughs in community empowerment efforts in the development of Small and Medium Enterprises (SMEs), in order to improve community welfare and regional income. The research method refers to qualitative research with a focus on efforts to develop SMEs through entrepreneurship and community empowerment. Micro, Small and Medium Enterprises should develop competitiveness through the use of digital platforms to be more effective, the use of online systems in buying and selling transactions, the use of digitalization to support various business activities to be more efficient, and the expansion of industrial networks that market their business results, in addressing the adequacy, harmony, and empowerment of the community in the development of Small and Medium Enterprises (SMEs). Building the entrepreneurial spirit of the community so that it is more attached and accustomed to digital-based SME activities, and continues to be optimized to help SMEs market their products in Makassar City and its surroundings. Optimization of SMEs is based on four indicators studied, namely: 1) Effectiveness, 2) Efficiency, 3) Adequacy, and 4) Harmony. The digital-based SME governance strategy is developed for professional SME actors by structuring, organizing, and controlling in developing the strength of the marketing and sales network. The government can make entrepreneurship a breakthrough to develop SMEs in order to advance regional income through various innovation policies that provide opportunities for the wider community to contribute to the development of SMEs.